Phosphonate as a Stable Zinc‐Binding Group for "Pathoblocker" Inhibitors of Clostridial Collagenase H (ColH). (16th March 2021) - Voos, Katrin; Schönauer, Esther; Alhayek, Alaa; Haupenthal, Jörg; Andreas, Anastasia; Müller, Rolf; Hartmann, Rolf W.; Brandstetter, Hans; Hirsch, Anna K. H.; Ducho, Christian
Abstract: Microbial infections are a significant threat to public health, and resistance is on the rise, so new antibiotics with novel modes of action are urgently needed. The extracellular zinc metalloprotease collagenase H (ColH) from Clostridium histolyticum is a virulence factor that catalyses tissue damage, leading to improved host invasion and colonisation. Besides the major role of ColH in pathogenicity, its extracellular localisation makes it a highly attractive target for the development of new antivirulence agents. Previously, we had found that a highly selective and potent thiol prodrug (with a hydrolytically cleavable thiocarbamate unit) provided efficient ColH inhibition. We now report the synthesis and biological evaluation of a range of zinc‐binding group (ZBG) variants of this thiol‐derived inhibitor, with the mercapto unit being replaced by other zinc ligands. Among these, an analogue with a phosphonate motif as ZBG showed promising activity against ColH, an improved selectivity profile, and significantly higher stability than the thiol reference compound, thus making it an attractive candidate for future drug development. Abstract : Stable "pathoblocker" : A series of compounds with non‐thiol (stable) zinc‐binding groups has been synthesised and tested for inhibition of the collagenase ColH, a key mediator of clostridial pathogenicity. The most promising compound, a phosphonate, was studied for selectivity over potential human off‐targets and its toxicity both in vitro and in vivo, and was shown to significantly reduce collagenase activity.